Political Economy of Renewable Energy and Regional Development: Understanding Social and Economic Problems of Biodiesel Development in Indonesia - Nuva, Nuva; Fauzi, Akhmad; Dharmawan, Arya Hadi; Kumala Putri, Eka Intan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
The transition of fossil fuel to non-fossil fuels (biodiesel fuel for diesel blending) has continued to evolve. The largest source of biodiesel’ raw materials in Indonesia derives from oil palm. Biodiesel development is also believed to generate benefit for society as well as for regional and national, including job creation, infrastructure improvement, revenue generation for governments and reduce national dependence on fossil fuels, and minimize adverse environmental fossil fuel impacts. However, despite its targets and strengthened by various comprehensive policies, the development of biodiesel in Indonesia also faces significant barriers. Descriptive analysis used in this study to understand the political economy of biodiesel engagement. The limited domestic market, mainly related to the issue of non-competitive prices with diesel, relatively low of oil prices, and high prices of fresh fruit bunches (FFB) are the constraints in the production of biodiesel for domestic uptake. The national political aspect related to the use of biodiesel by government parties, including non-PSOs, becomes an important issue in ensuring the sustainability of biodiesel. In addition, the issue of sustainability in the upstream (oil palm plantation) and dumping issues expressed by the EU and the US Government are also the main problems in Indonesian biodiesel export.